Examination of the element content of beers - Szabó, Edina; Andrási, Dávid; Sipos, Péter (Acta Agraria Debreceniensis, 2014)
Beer is a complex mixture of more than 800 several components, the most important ones are the minerals from this. Minerals originate especially from water and malt. In this work we measured the mineral contents of some own-brewed beer samples. We compared the results with the mineral contents of the water used as raw material of beer.